Performance study of a new smart hybrid parabolic trough collector system integrated with hybrid tubular thermoelectric generator. (25th June 2021) - Habchi, A.; Hartiti, B.; Labrim, H.; Fadili, S.; Benyoussef, A.; Belouaggadia, N.; Faddouli, A.; Benaissa, M.; Ntsoenzok, E.; EZ-Zahraouy, H.
Highlights: A new hybrid parabolic trough concentrator is proposed and analyzed. The theoretical model is presented, numerically simulated. The thermal and electrical performance of the new system are analyzed. The numerical model is validated based on a new validation method. Results showed an overall efficiency of 76.21% corresponding to 71.37 W as additional electrical power. Abstract: Advanced parabolic trough systems are the promising technologies for the production of usable heat and electrical power. Here we study the effects of hot water temperature adjustment concept and optical concentrator on the thermal and electrical efficiencies of a new PTC/HTTEG configuration, which comprises parabolic trough concentrator and hybrid tubular thermoelectric generator. The hybrid tubular thermoelectric generator (HTTEG) was integrated within the collector tube, where the hot water is passed between the inner side of the absorber tube and the top surface of the HTTEG. Meanwhile, to create a large temperature difference across the HTTEG sides, a cold water is passed along the inner side of the HTTEG. A low consumption pump was energized using HTTEG power in order to keep the hot water temperature at 95 °C for a long time (temperature adjustment concept). Numerical simulations show that the improvement in performance of the hybrid system highly depends on the adjustment concept and optical concentrator. As the solar concentration ratio increases, the overall efficiency of the hybrid system increases significantly to 76.21% and the amount of hot water reaches to a maximum value of about 846.77 Liter/Day for a concentration of 30 suns. Also, the power generated by the HTTEG and hot water temperature stay stable at 71.37 W and 95 °C, respectively, due to the hot water temperature adjustment effect. To validate the results of numerical model, a new validation method was proposed and discussed. The comparison of results obtained with results of the exact solution indicates a good agreement.